How to orchestrate a soccer team: Generalized synchronization promoted by rhythmic acoustic stimuli - Müller, Manfred A.; Martínez-Guerrero, Antonieta; Corsi-Cabrera, Maria; Effenberg, Alfred O.; Friedrich, Armin; Garcia-Madrid, Ignacio; Hornschuh, Matthias; Schmitz, Gerd; Müller, Markus F. (Frontiers in Human Neuroscience, 2022)
Interpersonal coordination requires precise actions concerted in space and time in a self-organized manner. We found, by using soccer teams as a testing ground, that a common time frame provided by adequate acoustic stimuli improves the interplay between teammates. We provide quantitative evidence that the connectivity between teammates as well as the scoring rate of male soccer teams improve significantly when playing under the influence of an appropriate acoustic environment. Unexpectedly, female teams do not show any improvement under the same experimental conditions. We show by follow-up experiments that the acoustic rhythm modulates the attention level of the participants with a pronounced tempo preference and a marked gender difference in the preferred tempo. These results lead to a consistent explanation in terms of the dynamical system theory, nonlinear resonances, and dynamic attention theory, which may illuminate generic mechanisms of the brain dynamics and may have impact on the design of novel training strategies in team sports.